Non-Hodgkin Lymphoma Presenting as Advanced Ovarian Cancer-Report of Three Cases - Tayfun Güngör; Serap Akbay; Özlem Altınkaya; Mustaf Özat; Ümit Bilge (Medical Network, 2009)
Primary origin for lymphoma is the lymph nodes, spleen and bone marrow. Extranodal sites are involved in more than 30% of the cases. Ovarian involvement by malignant lymphomas is well known as a late manifestation disseminated nodal disease. But, primary ovarian lymphoma and secondary ovarian involvement as initial manifestation of lymphoma are unusual. Clinical data of the three patients with non-Hodgkin lymphoma mimicking advanced ovarian cancer are presented. Preoperative imaging studies revealed pelvic solid masses suggesting an ovarian tumor and Ca-125 levels were elevated. The diagnosis of malignant lymphoma was established from the specimens after exploratory laparotomy. Less than 1% of patients with malignant lymphoma present with an ovarian mass. In the presence of an ovarian tumor, the possibility of lymphoma should be considered, and its clinical and biological signs should be actively sought. Although rarely encountered lymphoma should be included in the differential diagnosis of gynecologic malignancies because of a favorable outcome when properly diagnosed and treated.